Evaluation of the Costs and Outcomes of COVID-19 Therapeutic Protocols in Critically Ill Patients in Alzahra Hospital, Isfahan, Iran - Majid Davari; Sarah Mousavi; Mohammad Reza Maracy; Elahe Khorasani; Masih Zamani; Mohammadreza Amirsadri (Journal of Pharmaceutical Care)
Background: During the COVID-19 pandemic, different drug protocols were used to treat and manage patients. Considering the diversity in these protocols and the high costs associated with the disease, we aimed to evaluate the costs and effects of the most common therapeutic protocols among critically ill COVID-19 patients.